Answer:
The correct answer choice is D) 2.
Explanation:
To find the derivative of y with respect to x (dy/dx), we'll first need to use the chain rule for differentiation. The chain rule states that the derivative of a composite function is the derivative of the outer function multiplied by the derivative of the inner function.
Here, our function is y = ln(x^2 + y^2). Let's take the derivative with respect to x:
dy/dx = d/dx[ln(x^2 + y^2)]
= 1/(x^2 + y^2) * d/dx[x^2 + y^2]
= 1/(x^2 + y^2) * (2x + 2y * dy/dx)
We need to solve for dy/dx, so let's rearrange the equation:
dy/dx * (1 - 2y/(x^2 + y^2)) = 2x/(x^2 + y^2)
dy/dx = 2x/(x^2 + y^2 + 2y)
Now, let's substitute the point (1,0) into the equation:
dy/dx = 2*1/(1^2 + 0^2 + 2*0)
= 2/1
= 2
So, the value of dy/dx at the point (1, 0) is 2.